The effects of dantrolene in the presence or absence of ryanodine receptor type 1 variants in individuals predisposed to malignant hyperthermia. Issue 4 (July 2022) - Noda, Yuko; Mukaida, Keiko; Miyoshi, Hirotsugu; Nakamura, Ryuji; Yasuda, Toshimichi; Saeki, Noboru; Nishino, Ichizo; Tsutsumi, Yasuo M
Abstract: Dantrolene is currently the only drug known to specifically treat malignant hyperthermia (MH) crises. Although dantrolene attenuates Ca 2+ disorders by acting mainly on the ryanodine receptor type 1 (RYR1), some patients who manifest MH without RYR1 variants have also been successfully treated with dantrolene. Thus, dantrolene appears to have an inhibitory effect on patients with and without RYR1 variants. This study aimed to investigate whether the effects of dantrolene differed depending on the presence or absence of RYR1 variants using muscle cells from MH-predisposed individuals. The study participants were individuals diagnosed with MH predisposition by the Ca 2+ -induced Ca 2+ release rate test. They were genetically tested and divided into two groups: with and without RYR1 variants. We investigated whether these two groups showed differences in the changes in the half-maximal effective concentration (EC50 ) for caffeine and the resting intracellular Ca 2+ concentration ([Ca 2+ ]i ) before and after dantrolene administration. Dantrolene administration significantly increased the EC50 ( P  < 0.0001) and decreased the resting [Ca 2+ ]i ( P  < 0.0001). The inhibitory effects of dantrolene and the presence of RYR1 variants showed no statistically significant interactions related to the EC50 ( P  = 0.59) and resting [Ca 2+ ]i ( P  = 0.21). In conclusion, the presence or absence of RYR1 variants does not appear to influence the effect of dantrolene.